Commentary: The Changing Face of Dentistry. (October 2022) - LeResche, L.
The articles in this issue represent the final reports of 4 panels convened for the 2021 Arcora Distinguished Professorship in Dentistry Symposium at the University of Washington under the theme, "The Changing Face of Dentistry." The articles provide a range of perspectives on broad social, economic, and technological trends that have implications for the future of dentistry, defined as including not only dental practice but also dental education, organized dentistry, and dental research. Some common trends were identified in multiple groups, but the perspectives on these trends differed from group to group and sometimes even among panel members in the same group. In this Commentary, I briefly summarize and comment on the findings of each panel, then discuss and provide perspectives on 7 common themes addressed by multiple groups: acceleration of technological change; remote care/teledentistry; disparities and inequities in health and access to health care; the aging population and increased number of persons with multiple chronic conditions; convergence of data science, artificial intelligence, and machine learning; integration of dental and medical primary care; and changing payment systems, including value-based care. Finally, the implications of these findings for translational research are discussed. Knowledge Transfer Statement: This article reviews social, economic, and technological trends affecting the future of dentistry. These trends have important implications for the training of dentists and the organization of dental care with the aim of improving the oral health of the public. Clinical and translational research has an essential role to play in developing the interventions and evidence base for these improvements.